Tidal activity rhythms and depth distribution of rocky shore fish in an altered intertidal environment - Faria, Cláudia Barreiros Macedo de (2013)
In this note we report on changes of activity level of littoral fish and their use of different microhabitats in an altered intertidal environment, where intertidal fish are never emersed and turbulence is confined to high tides. Despite these atypical conditions, the structure of the assemblage is basically the same found in a typical rockyshore situation. Two intertidal fish known to possess internal tidal rhythms, Lipophrys pholis and Coryphoblennius galerita, retain those rhythms in these altered conditions, and the associated social changes in L. pholis are also retained. These observations support the studies of Gibson (1971), who showed that changes in hydrostatic pressure were of prime importance in keeping the tidal rhythm entrained. The subtidal Parablennius pilicornis, on the contrary, is more active during low tide than at high tide. The hypothesis that some subtidal species are excluded from the intertidal by a turbulence-avoiding mechanism is discussed.